2016
DOI: 10.1016/j.bjm.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance and ESBL-producing Salmonella spp. isolated from broiler processing plants

Abstract: The aim of this study was to investigate the occurrence of multidrug-resistant, extended spectrum beta-lactamase (ESBL) producing Salmonella spp. isolated from conveyor belts of broiler cutting rooms in Brazilian broiler processing plants. Ninety-eight strains of Salmonella spp. were analyzed. Multidrug resistance was determined by the disk diffusion test and the susceptibility of the isolated bacteria was evaluated against 18 antimicrobials from seven different classes. The double disk diffusion test was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 33 publications
3
19
3
1
Order By: Relevance
“…This result is in agreement with those obtained by other authors, which found reduced efficacy of this antimicrobial against salmonellae, maybe because of the indiscriminate use in humans and animals therapy [40][41][42].…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with those obtained by other authors, which found reduced efficacy of this antimicrobial against salmonellae, maybe because of the indiscriminate use in humans and animals therapy [40][41][42].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the most frequent profile of the isolates was weak biofilm formation and resistance to quinolones, sulfonamides, tetracyclines, cephalosporin, and penicillins (Figure 1). On the other hand, Ziech et al (2016b), evaluating Salmonella sp. strains isolated in broiler processing plants, detected 86% multiresistant strains, and the most frequent profile was weak biofilm formation, production of wide-spectrumbetalactamase, and resistance to beta-lactams, quinolones, and tetracyclines.…”
Section: Resultsmentioning
confidence: 99%
“…However, the widespread use and even abuse of antibiotics in animal husbandry have facilitated the emergence and dissemination of antibiotic resistance in Salmonella , which has posed a serious challenge for the health of animals and humans ( Marshall and Levy, 2011 ; Mukerji et al, 2017 ). Noticeably, numerous studies in recent years have indicated that extended-spectrum β-lactamase (ESBL)-producing Salmonella has been frequently isolated from food-producing animals and animal-derived foods in many countries of the world, including China ( Wu et al, 2013 ; Chon et al, 2015 ; Franco et al, 2015 ; Hu et al, 2015 ; Noda et al, 2015 ; Ziech et al, 2016 ; Zhao et al, 2017 ). ESBL-producing Salmonella is able to inactivate and hydrolyze the β-lactam ring in β-lactam antibiotics and third- and fourth-generation cephalosporins, leading to the increase of treatment cost and even to therapy failure, which has triggered a serious public concern ( Bonnet, 2004 ; Pitout and Laupland, 2008 ).…”
Section: Introductionmentioning
confidence: 99%